Central body fatness is a stronger predictor of cancer risk than overall body size - Amanda M. Barberio (Nature Portfolio, 2019)
Obesity is linked to increased cancer risk but the impact of body size versus weight distribution in determining the increased risk is unclear. Here the authors examined body mass index, waist circumference, and waist to hip ratio in relation to all-cancer incidence and incidence of seven individual cancers in a population of approximately 26,000 individual and conclude that central adiposity appears to be a stronger predictor of all-cancer risk than body size.